Prevalence, risk factors, psychological effects of children and adolescents with lower urinary tract symptoms: a large population-based study - Liu, Xingchen; Wang, Zhan; Zhou, Zhaokai; Yang, Shuai; Yang, Jing; Wen, Yibo; Zhang, Yanping; Lv, Lei; Hu, Jinhua; Wang, Qingwei; Lu, Wei; Wen, Jian Guo (Frontiers in Pediatrics, 2024)
Background Lower urinary tract symptoms (LUTS) are clinically frequent and seriously affect the psychological and mental health of children and adolescents.However, most studies on LUTS and its influence on the psychological behavior and mental health have focused on adults. This study aimed to investigate LUTS prevalence and associated factors in children and adolescents and explore its impact on psychological behavior.From October 2019 to November 2021, an epidemiological LUTS survey was carried out on 6077 children aged 6-15 years old in 12 primary and secondary schools in China by using anonymous questionnaires.Results A total of 5500 valid questionnaires were collected, and the total prevalence of four representative symptoms of LUTS: urgency, frequency, daytime urinary incontinence, and nocturnal enuresis was 19.46%, 14.55%, 9.75%, and 8.4%, respectively. The prevalence decreased with age, which decreased rapidly in children aged 6-12 years old. The incidence of LUTS in those who did not continue to use disposable diapers (DD) and began to perform elimination communication (EC) after the age of 1 was significantly higher than that of those who stopped using DD and started EC before one year of age (P < 0.05). There were significant differences in the occurrence of LUTS without toiled training (TT) (P < 0.05). The prevalence of LUTS in males was significantly higher than in females (P < 0.05). LUTS in children and adolescents with constipation was significantly higher compared to those without constipation (P < 0.05). The detection rate of abnormal psychological behavior in the LUTS group was 44.6%, which was significantly higher than that in the no LUTS group. The scores of emotional symptoms, conduct problems, hyperactivity, and peer communication problems were significantly higher in the LUTS group than the control group.In Mainland China, the prevalence of LUTS in children and adolescents is high. Continued use of DD after one year of age, history of urinary tract infection,lack of TT, and constipation were risk factors for LUTS. EC before one year of age is a protective factor for LUTS. The prevalence of psychological behavioral abnormalities is high in children and adolescents with LUTS, which needs to be more concerned.